Answer:
see explanation
Explanation:
1
Given
5x² - 50x + 120 ← factor out 5 from each term
= 5(x² - 10x + 24)
To factor the quadratic
Consider the factors of the constant term (+ 24) which sum to give the coefficient of the x- term ( - 10)
The factors are - 4 and - 6, since
- 4 × - 6 = 24 and - 4 - 6 = - 10, hence
x² - 10x + 24 = (x - 4)(x - 6) and
5x² - 50x + 120 = 5(x - 4)(x - 6) → d
2
64x² - 1 ← is a difference of squares and factors in general as
a² - b² = (a - b)(a + b)
64x² = (8x)² ⇒ a = 8x and b = 1
64x² - 1
= (8x)² - 1² = (8x - 1)(8x + 1) → b